Development Application of Composite Indices (CI): An Emerging Method to the Disciplines of Engineering, Economics and Finance - Putcha, Chandrasekhar; Sloboda, Brian W.; Khani, Mohammadreza (European Scientific Journal, ESJ, 2016)
Interdisciplinary or multidisciplinary research involves the use of a combination of principles from various disciplines: engineering, economics, finance, etc. This particular approach makes a lot of sense; otherwise, all the research will become compartmentalized, and researchers from one discipline will not know what researchers from other disciplines are doing and how those principles can be applied to their own disciplines. One way to create a common base connecting all these disciplines is to use the concept of composite indicators (CI), which is an emerging field of study. The use of composite indices, as part of an emerging method, for research problems in various fields allows for greater understanding of research problems and provides a visionary approach to solve such problems. This paper first states the existing methods for calculation of composite indicators in the literature and then suggests a new method.